Scalable quality of service multicast routing protocol for mobile ad hoc networks - Qabajeh, Mohammad M. M. (Kulliyyah of Engineering, International Islamic University Malaysia, 2012)
Mobile Ad hoc Networks (MANETs) have gained significant interest and popularity since they have enormous potential in several fields of applications. Infrastructure-free, self-configuring and mobility are the main reasons behind this popularity. As the necessity of the group-oriented applications over MANET increases, Quality of Service (QoS) support is getting attention as one of the critical issues. Multicast communication is the ideal communication technique for supporting these types of applications. However, QoS multicast routing in large-scale networks faces several difficulties and challenges that need to be addressed. These challenges include dynamic MANET topology, multicast packet forwarding and shared wireless medium. Thus, it is necessary to design an efficient multicast routing protocol to support multimedia multicast applications in large networks with large group sizes. In this research, the problem of scalability of multicast routing protocols to support QoS over MANETs is investigated. In particular, a new Scalable QOS Multicast Routing Protocol (SQMRP) has been developed. The main objective of this protocol is to design a lightweight scalable QoS multicast routing scheme irrespective of the number of multicast members and network size. This is achieved by applying the following strategies: First, designing a novel and scalable virtual architecture that takes advantage of the geometric information of the mobile nodes, which provides efficient cluster management to handle dynamic movement of mobile nodes. Second, developing a new location service algorithm which reduces redundant propagation of packets between clusters. Third, proposing a simple and efficient hierarchical structure to manage the multicast members to further enhance the scalability. And finally, setting up a multicast forwarding tree through developing a route discovery algorithm guided by the geographic information which incurs lower overhead. The performance of the proposed protocol is evaluated through developing both an analytical investigation and extensive simulation using the GloMoSim simulator environment. The obtained results are compared with the well-known multicast protocol On-Demand Multicast Routing Protocol (ODMRP). It has been found that the proposed virtual construction can scale to large MANETs and effectively reduces the communication overhead for location service and multicast routing discovery. The simulation results showed that, the average PDR of SQMRP is higher by 7.9% and the NPO is reduced by an average of 57.7% compared to ODMRP considering different network sizes. Also, PDR is improved by 8.3% and the NPO is reduced by 55.6% for different multicast group sizes. In fact, it is observed that SQMRP out performs ODMRP protocol in most of the studied metrics and scenarios.